FICTIONAL REPRESENTATION OF WOMEN SYMBOLIZING CONTEMPORARY VALUES IN SPECIAL REFERENCE TO NATALIE HAYNES “PANDORA’S JAR” - Durgavyshnavi, G.; Vijayanand, Dr.A. (The journal of contemporary issues in business and government, 2023)
The present paper focuses on Fictional Representation of women symbolizing contemporary values in special reference to Natalie Haynes “Pandora’s Jar”. In Pandora's Jar: Ladies in the Greek Fantasies, Natalie Haynes, classicist, author, and telecaster, tries to reevaluate a portion of the persevering through impression of ladies from Greek fantasy. Haynes places ladies whose accounts have generally been kept to a great extent in the shadows, up front stage with her top to bottom investigation and reassessment of their heritages. In this book Haynes presents an open and provocative assortment of expositions, blending grant and a gnawing mind borne from her experience as a professional comic. Natalie Haynes picks ten ladies in Greek fantasies whose accounts have been told and retold, in artworks, containers, films, dramas, musicals. She saw that significant ladies characters in the first adaptations became nonexistent or pale shadows of themselves as time elapsed and with each retelling. The stores as told in the movies are the rendition that the vast majority see, recollect and accept. In this captivating book she retells the narrative of these ten Greek legendary ladies, dives into old texts and closer views them.